A relação do perfil dos gestores e escolas privadas e seu desempenho organizacional em Curitiba/PR - Pitta, Marco Aurelio (2020)
Basic (Primary and Secondary) Education in Brazil has undergone several changes in recent years. The importance that this sector has in the economy is demonstrated by the numbers that influence the whole society. According to the MEC, in 2018, private basic education had nearly 9 million students enrolled across the country. In this study, we chose to choose as a scope the organizations in this sector in Curitiba, Paraná. The main objective of this research is to evaluate some relationships of constructs such as the profile of the main school manager, the level of use of management tools, mainly related to financial management, as well as the reflection of these variables in the school's organizational performance. The variation in the number of students enrolled in private schools between 2015 and 2018 was the main indicator considered for purposes of organizational performance. This dissertation sought theoretical references that could support the research with emphasis on theoretical studies of the profile of school managers and financial management, where we were able to analyze various contributions to the functioning of an organization and the influence suffered by its management. Other theories related to the manager's profile, such as knowledge, academic education and professional experience, also influenced several conclusions of the research. It was also possible to build an important contribution in relation to the level of use of financial management tools. Several theoretical advances can be demonstrated in relation to these constructs. In methodological terms, this quantitative research was carried out through the elaboration of a questionnaire distributed to 485 private schools in Curitiba. In the end, 87 schools participated, which collaborated with an important management study that sought to prove whether this construct had any influence on the performance of the number of students in the schools they manage during the years 2015 to 2018. There were five hypotheses of relationships statistically tested through the SPSS statistical tool that could bring several reflections and findings to the management of private primary schools. Among the hypotheses, the one that proved most reliable, statistically proven is that there is a significant influence between the academic profile of the main manager of a private school and the organizational performance, considering the variation in the number of students enrolled in the period. The practical results of this study can be used for investments in the management area of private schools. Under the theoretical aspect, they will be able to contribute to future research in the area of education and training of the main professionals who lead this type of organization.